Metode Penulisan Sejarah Kitab Tarikh Al-Umam Wa Al-Muluk Karya Al-Thabari: Indonesia - Alamshah, Anisah; Pababbari, Musafir; Syukur, Syamzan (Universitas Islam Negeri Alauddin Makassar, 2023)
Tarikh al-Umam wa al-Muluk, also known as Tarikh al-Rusul wa al-Muluk, is a significant work in Islamic historiography.While it is widely acknowledged as a primary source in classical Islamic studies, it has been criticized for its perceived lack of systematic and interpretative style. Consequently, there has been a preference for Orientalist works that are deemed more rational and critical. This research study uses a descriptive-analytical approach to delve into the life and writings of Al-Thabari, a prominent scholar of the Abbasid era. The study suggests he was born in 225 AH and died in 310 AH, with his work heavily influenced by his socio-political context. Tarikh al-Umam wa al-Muluk